Cortical lesion load correlates with diffuse injury of multiple sclerosis normal appearing white matter. (February 2014) - Mistry, Niraj; Abdel-Fahim, Rasha; Mougin, Olivier; Tench, Christopher; Gowland, Penny; Evangelou, Nikos
Background: Degeneration of central nervous system normal appearing white matter (NAWM) underlies disability and progression in multiple sclerosis (MS). Axon loss typifies NAWM degeneration. Objective: The objective of this paper is to assess correlation between cortical lesion load and magnetisation transfer ratio (MTR) of the NAWM in MS. This was in order to test the hypothesis that cortical lesions cause NAWM degeneration. Methods: Nineteen patients with MS underwent 7 Tesla magnetisation-prepared-rapid-acquisition-gradient-echo (MPRAGE), and magnetisation transfer ratio (MTR) brain magnetic resonance imaging (MRI). Cortical lesions were identified using MPRAGE and MTR images of cortical ribbons. White matter lesions (WMLs) were segmented using MPRAGE images. WML maps were subtracted from white matter volumes to produce NAWM masks. Pearson correlation was calculated for NAWM MTR vs cortical lesion load, and WML volumes. Results: Cortical lesion volumes and counts all had significant correlation with NAWM mean MTR. The strongest correlation was with cortical lesion volumes obtained using MTR images ( r = −0.6874, p = 0.0006). WML volume had no significant correlation with NAWM mean MTR ( r = −0.08706, p = 0.3615). Conclusion: Our findings are consistent with the hypothesis that cortical lesions cause NAWM degeneration. This implicates cortical lesions in the pathogenesis of NAWM axon loss, which underpins long-term disability and progression in MS.